Marketing management - Marshall, Greg W.; Johnston, Mark W. (New York, NY : McGraw-Hill Education, 2023)
"No doubt about it, marketing is really changing. Marketing today is: Very strategic-customer-centricity is now a core organizational value. Practiced virtually, digitally, and socially to a greater degree than ever before imagined. Enabled and informed by analytics and new technologies. Accountable to top management through diligent attention to metrics and measurement. Oriented toward service as driver of product. "Owned" by everybody in the firm to one degree or another"--
Includes index.
Keywords: Marketing -- Management